The Scope of the Right to Free Development of the Personality in Manuals for Coexistence at Educational Establishments Abstract - Rojas Castillo, Zaida Maritza; Acevedo Suárez, Aurymayerly (DIXI, 2015)
The right to free development of the personality has its origins in the Universal Declaration of Human Rights and is enshrined in Article 16 of the National Constitution as a fundamental right that affcts other rights because of the strength of its content. It has also been raised to the category of a principle by the Constitutional Court based on this argument. Given the importance of this precedent, this article aims to randomly review certain manuals for coexistence in the municipality of Piedecuesta (Santander Department), analyzing provisions that are in violation of the Constitution. The Constitutional Court has reiterated that student regulations or manuals for coexistence must be in accordance with the framework of the National Constitution and international treaties, in order to ensure respect for human rights. If they are not in accordance, they must be modifid and adjusted according to constitutional principles. Here the tutela, or injunctive action, plays an important role as a mechanism for constitutional protection that makes it possible to safeguard the right to free development of the personality and, if necessary and required, empowers the tutela judge to order modifiation of the manual for coexistence.